Genome-wide identification and functional validation of RLCK VII subfamily genes conferring disease resistance in broad bean (Vicia faba L.) - Wang, Fan; Liu, Chenwei; Lu, Hongchen; Xu, Renchao; Bian, Xiaochun (Frontiers in Plant Science, 2026)
IntroductionMembers of receptor like cytoplasmic kinase VII (RLCK VII) subfamily are important participants in plant growth and development, innate immunity, and resistance to abiotic stress. However, in broad beans, the regulatory mechanisms of RLCK VII subfamily genes involved in these processes remains unclear.MethodsTo further elucidate the regulatory mechanisms, a comprehensive whole-genome analysis was conducted. To investigate the disease resistance function of VfRLCK VII genes, their expression patterns under infection by Alternaria alternata were analyzed through transcriptome sequencing. And functional validation of VfRLCK VII4 (VfRLCK176) was performed via transformation into Nicotiana tabacum (tobacco).ResultsVfRLCK VII subfamily comprised 45 members, which were unevenly distributed across 6 chromosomes. These genes encoded protein sequences ranging from 296 to 595 aa in length, with 39 located in the nucleus and 6 in chloroplasts. VfRLCK VII proteins were classified into 9 subgroups and 3 members, all of which contained only a single PKc_like superfamily domain. Promoter analysis indicated that VfRLCK VII genes possessed various cis-acting elements, including light responsive elements, plant hormone responsive elements, stress responsive elements, and growth and development regulatory elements. Among them, 21 genes exhibited differential expression level, which might be involved in the disease resistance function of broad beans. The disease resistance assessments demonstrated that after inoculation with A. alternata, transgenic tobacco plants displayed milder symptoms and significantly smaller lesion areas compared to wild type controls. This finding suggested that VfRLCK VII4 could positively regulate tobacco's resistance to A. alternata.DiscussionThis study provides novel insights into the RLCK VII-mediated defense network and offers candidate genes for breeding disease-resistant broad bean varieties.